Valuasi Perusahaan Berdasarkan Data Keuangan Dan Non Keuangan (Studi Kasus Pada PT. Berita Bali Media) - Ni Made Estiyanti (Primakara University, 2019)
The role of Information and Communication Technology in supporting operational and managerial systems in government agencies today is felt to be increasingly important. With the significant developments in this field, it has led to various fundamental changes in all aspects, where information has become a very valuable and decisive commodity to achieve the success of running a government in a comprehensive sense. The era of globalization, advances in Information and Communication Technology (ICT) and efforts to improve the performance of government agencies have encouraged the transformation of Government towards e-Government. The transformation of the manual governance work process system into an electronic-based work system is carried out through the use of ICT. Utilization of ICT includes activities related to data processing, information management, management systems and electronic work processes. Thus, to realize this transformation, it is necessary to develop e-Government. And now the implementation of e-Government has been implemented in almost all countries so that it has the opportunity to accelerate economic growth, increase people's welfare dramatically, and strengthen good governance practices. While utilization and development related to the use of information and communication technology in e-Development. E-Development has interrelated elements including e-Leadership along with institutional policies and arrangements, information and communication infrastructure, e-Government, e-Society and the supporting ICT industry. Efforts to develop e-Development have been made, although limited to only a few fields. The development of e-Development has received support from related government agencies such as DEPKOMINFO, the Ministry of Research and Technology and the Agency for the Assessment and Application of Technology.